2005
DOI: 10.1177/0091270005280445
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Taste Disturbance by Losartan and Perindopril in Healthy Volunteers

Abstract: The aim of this study was to compare the degree of taste disturbance by losartan, an angiotensin II receptor blocker, with that of perindopril, an angiotensin-converting enzyme inhibitor. Perindopril erbumine (2 mg), losartan potassium (25 mg), or vehicle was given to Japanese volunteers (n = 7) for 14 days in a randomized, placebo-controlled, 3-way crossover design with a 14-day washout period. Gustometry by filter-paper test and electrogustometry were performed before and at the end of each trial. Plasma ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…6 The role of ACE2 in modulating taste perception has been highlighted in many studies analyzing the chemosensitive side effects of ACE2 inhibitors and angiotensin II blockers. 7,8 The mechanism by which ACE2 inhibitors cause taste disturbance is unclear but does not appear to be related to any alteration in serum 7,8 and saliva 7 zinc levels. Presumably, these drugs inactivate the Gprotein-coupled proteins and sodium-ion channels present in the taste receptors.…”
Section: Ageusiamentioning
confidence: 99%
“…6 The role of ACE2 in modulating taste perception has been highlighted in many studies analyzing the chemosensitive side effects of ACE2 inhibitors and angiotensin II blockers. 7,8 The mechanism by which ACE2 inhibitors cause taste disturbance is unclear but does not appear to be related to any alteration in serum 7,8 and saliva 7 zinc levels. Presumably, these drugs inactivate the Gprotein-coupled proteins and sodium-ion channels present in the taste receptors.…”
Section: Ageusiamentioning
confidence: 99%
“…In the current study, the subjects had no recent history of somatic disorders that are known to alter gustatory function. About 170 drugs, either alone or in combination, are reported to be associated with taste disturbances (Nolan, 2001;Schiffman, 1991;Tsuruoka et al, 2004Tsuruoka et al, , 2005. Angiotensin-converting enzyme (ACE) inhibitors and decreased Zn in the blood are well-known causes of taste disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one has to consider the taste disturbance caused by angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin-2 receptor blockers (ARBs). 2,3 The authors reported that ACEIs and/or ARBs were prescribed for 72% of the patients with CKD. This could explain the higher taste thresholds in CKD.…”
Section: Taste Disturbance By Angiotensin-converting Enzyme Inhibitormentioning
confidence: 99%